THE CONTACT PARAMETERS OF THE ROLLING STOCK AND THE PERMISSIBLE SPEED DECISION BRAKE PROBLEM ON THE TRANS-SHIPPING AREAS - Korzhenevych, I. P.; Todua, T. Gh.; Toropov, B. I. (Science and Transport Progress, 2008)
Influence of the rolling stock parameters on the maximally permissible train traffic speeds according to the conditions of emergency braking on mountain pass sections is under consideration.